Isyarat Al_Qur'an Tentang Kecerdasan Sebagai Keimanan dan Amal Saleh - Iwan Satiri; Alber Oki; Abdullah Safei (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2021)
The fact that not everyone who is intellectually high, able to control emotions and has good spiritual abilities is an interesting problem to research. Answering this problem links intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ) hinted at in the Qur'an. Intelligence as faith and righteous charity as in QS. al-Ashr/103:13 covers intellectual intelligence, emotional intelligence, and spiritual intelligence. So the conclusion is that if intelligence as a faith that is able to think logically and justify in the heart that Allah SWT as God who should be worshipped and Prophet Muhammad (peace be upon him) as His messenger, then this ability is a form of intellectual intelligence (IQ). And if the intelligence of godly charity becomes the ability to behave well that is useful for the perpetrator and others for the sake of the interests of the world and the hereafter, then this ability is a form of emotional intelligence (EQ) accompanied by spiritual intelligence (SQ).